SIPADU MATURITY LEVEL EVALUATION USING COBIT 4.1: CASE STUDY OF GEOSPATIAL INFORMATION AGENCY - Imam W Sukoco; Irman Hermadi; Hendro Sasongko (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
Public financial management transparency and accountability is one of the implementations of good governance. The Geospatial Information Agency (BIG) has developed the Integrated Budget Implementation Information System (SIPADU) application to monitor the government's financial management to achieve accountable and transparent financial management. SIPADU has been built and used, but its implementation has not yet achieved an optimal function. This study found that it is related to the SIPADU management evaluation, maturity level, and SIPADU governance improvement. This study aimed to analyze SIPADU maturity level using the COBIT 4.1 approach. The sampling method used was purposive sampling, and the respondents were users and administrators of SIPADU. Interviews were conducted, in addition to the questionnaire results measurement. The data were calculated to determine the maturity level. The results showed that the SIPADU maturity level was still level 3 below the expected level, namely level 4. The agency's management is recommended to develop SIPADU. Keywords: COBIT 4.1, Level of Maturity, SIPADU